2005
DOI: 10.4028/www.scientific.net/msf.475-479.1651
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Ceramics Ti<sub>3</sub>SiC<sub>2</sub>: Combustion Synthesis and the Reaction Mechanism

Abstract: In this study, Ti3SiC2 was successfully synthesized by the combustion of green samples with a composition formula: (3-x)Ti/Si/(2-x)C/xTiC, where x ranged from 1.0 to 1.8. First, the Ti3SiC2 yield monotonically increased with x, but the maximal yield was less than 50%. The most important factor to increase the Ti3SiC2 yield was found to be the post-combustion heating. The yield dramatically increased to about 90% when a 150-second post-combustion heating time was provided. Furthermore, the yield was proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Moreover, Lis et al 15,29 and Khoptiar and Gotman 18 have shown that, for high heating rates of the reactants (500 K/s in their case), metallic reactants rapidly melt and form a Ti-Si liquid phase. Such a Ti-Si liquid phase is also supported by the work of Huang and Chen 27 and is the base of the so-called temperature fluctuation procedure developed by Zhang et al 30 The absence of a liquid signature in our TR-XRD analysis likely results from the low penetration depth of the Xray beam (beam energy is about 4.9 keV to avoid the Ti fluorescence), from the flow of the liquid phase through the pores of the medium or from the low volume fraction of the liquid phase.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Moreover, Lis et al 15,29 and Khoptiar and Gotman 18 have shown that, for high heating rates of the reactants (500 K/s in their case), metallic reactants rapidly melt and form a Ti-Si liquid phase. Such a Ti-Si liquid phase is also supported by the work of Huang and Chen 27 and is the base of the so-called temperature fluctuation procedure developed by Zhang et al 30 The absence of a liquid signature in our TR-XRD analysis likely results from the low penetration depth of the Xray beam (beam energy is about 4.9 keV to avoid the Ti fluorescence), from the flow of the liquid phase through the pores of the medium or from the low volume fraction of the liquid phase.…”
Section: Discussionmentioning
confidence: 58%
“…Such a first step of the reaction between Ti-Si-C reactant mixtures is in very good agreement with different observations previously performed by other authors. 14,27,28 During the heating of the (3Ti1Si12C) powder blend up to t 2 , TR-XRD analyses do not indicate any other solid state reaction; neither Ti 5 Si 3 18 nor Ti 5 Si 3 C x 17 intermediate phases were detected. To our knowledge, Ti 5 Si 3 C x is always formed as an intermediate phase when SiC is used as silicon source.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations